2013
DOI: 10.22452/adum.vol20no2.4
|View full text |Cite
|
Sign up to set email alerts
|

Oral health related quality of life and periodontal status of a selected Malaysian adult population: A pilot study

Abstract: Aim: To assess the oral health related quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…BPE was first introduced over 30 years ago and is widely used not only in the UK but also other countries, including Malaysia, on account of its ability to screen patients for systematic periodontal management. 12,[19][20][21] The Malaysian National Oral Health Survey for Adults reported that 94% of all Malaysians are affected by periodontal disease at various levels. 22 However, according to the BPE of the participants in the current study, none of the participants had healthy periodontia.…”
Section: Discussionmentioning
confidence: 99%
“…BPE was first introduced over 30 years ago and is widely used not only in the UK but also other countries, including Malaysia, on account of its ability to screen patients for systematic periodontal management. 12,[19][20][21] The Malaysian National Oral Health Survey for Adults reported that 94% of all Malaysians are affected by periodontal disease at various levels. 22 However, according to the BPE of the participants in the current study, none of the participants had healthy periodontia.…”
Section: Discussionmentioning
confidence: 99%
“…For this cross‐sectional study, hypothesis test for two population proportions was used to calculate the sample size. To calculate the sample size, data from a study that had used the Malaysian version of the Oral Health Impact Profile (OHIP)‐14 scale to determine the association between periodontal status and OHRQoL were considered. Using the prevalence of ‘food lodging’ in those with a healthy periodontium/gingivitis (18%) and periodontitis (31%) reported in that study, for a level of significance of 5% and a power of 80%, a minimum of 171 participants were needed per group.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the effectiveness of these measures in controlling the prevalence of periodontitis among adults in Malaysia between 2010 and 2020, small local studies were searched to obtain a more recent report on prevalence of periodontitis among adults in Malaysia. Four local studies published after 2010 were identified [ 13 16 ]. Despite systemic diseases being highly associated with periodontitis, the findings from these studies, which focused on populations with systemic diseases or health conditions, did not differ significantly from those reported in NOHSA 2010.…”
Section: Methodsmentioning
confidence: 99%